Immunostaining patterns of myoepithelial cells in breast lesions: a comparison of CD10 and smooth muscle myosin heavy chain. Issue 6 (27th May 2004) - Kalof, A N; Tam, D; Beatty, B; Cooper, K
Abstract : Background: Recent studies have reported CD10 expression in myoepithelial cells (MEC) of the breast, supporting its use as a marker to help distinguish invasive breast carcinoma (IC) from ductal carcinoma in situ (DCIS). Aim: To compare the effectiveness of CD10 with smooth muscle myosin heavy chain (SMMHC) in the detection of MEC in benign and malignant breast lesions. Methods: Histological material from 25 patients with DCIS and 21 with IC were immunostained for CD10 and SMMHC. Staining was scored on a scale of 0 to 3+ (0, no staining; 3+, intense) and the staining distribution was documented as focal, partial, or circumferential. Results: Uniform, 3+ circumferential CD10 and SMMHC staining of MEC was seen in normal breast ducts and lobules, and in ducts and acini involved in sclerosing adenosis and apocrine metaplasia. In an analysis of total ducts involved by DCIS, 3+ circumferential staining was seen in 65 of 366 ducts (17.7%) stained for CD10 versus 190 of 396 ducts (48%) stained for SMMHC. MEC were not detected immunohistochemically in 116 of 366 ducts (31.7%) with anti-CD10 and 50 of 396 (12.7%) with anti-SMMHC. In contrast, all ICs were negative for both CD10 and SMMHC. Focal background staining of stromal myofibroblasts was seen with both CD10 and SMMHC, but CD10 showed a higher rate of non-specific staining of epithelial cells. Conclusion: Although CD10 can aid in the distinction between IC and DCIS, SMMHC is a more sensitive and specific marker of MEC and shows less heterogeneity of immunostaining patterns.